PENGARUH RASIO KEUANGAN TERHADAP PROFITABILITAS PERBANKAN DI INDONESIA - Widowati, Sari Ayu; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
In general, profitability or rent-ability is the capability of a company in generating profit during a certain period. The profitability of the company describes the comparison between profits and the assets or capital which generates its profit. The purpose of this research is to test the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non Performance Loan (NPL). The samples are 28 banking companies that have been selected by using purposive sampling from the research population i.e. the entire banking companies which are listed in Indonesia Stock Exchange (IDX) from 2010 to 2013. The classic assumption test and the multiple regressions analysis with the assistance of SPSS 20 version has been used as the statistics test instruments. The result of the result describes that overall the regressions model of this research has met the classic assumption test, which means that the regressions model of this research is free from any symptoms of multicolinearity, heteroscedasticity, autocorrelation and the generated data has been normally distributed. The multiple regressions analysis describes that Capital Adequacy Ratio (CAR) has significant and negative influence to the profitability, Loan to Deposit Ratio (LDR) has not significant and positive influence to the profitability, Non Performance Loan (NPL) has significant and negative influence to the profitability. Keywords: Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performance Loan (NPL), and Profitability